Viewpoint: 50 Years of Pascal. - Wirth, Niklaus (Communications of the ACM, 2021)
A retrospective on the fifty-year history of the Pascal programming language is offered. The author discusses his role in a working group developing the Algol 60 programming language as well as the subsequent Algol W language with a focus on the modifications to Algol which resulted in his development of Pascal. The distribution of Pascal to schools and universities is described along with its successor languages and the alleged dissolution of the hardware-software dichotomy.